Construction of Patient Specific Virtual Models of Medical Phenomena - Potocnik, B.; Heric, D.; Zazula, D.; Cigale, B.; Bernad, D.; Tomažic, T. (Informatica)
Construction of Patient Specific Virtual Models of Medical Phenomena